Highly dispersed Ni-Mo encapsulated in hollow mesoporous ZSM-5 as an efficient catalyst for tetralin conversion to light aromatics - Mengdi Wang; Limin Zhang; Haoqing Zhang; Jiaming Wu; Keyan Li; Xinwen Guo (Fuel, 2026)

Elevation dependence of vegetation phenology on the southeastern margin of the Tibetan Plateau - Tiantian Yang; Zheneng Hu; Wanxiong Zhang; Jingjing Wang; Zhongshi Zhang; Keyan Fang; Xin Zhou; Jie Zhou; Zhuoya Zhang; Zhengtang Guo (Science China Earth Sciences, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

Spatiotemporal prediction and differentiated governance of coal mining subsidence in the desert-loess transition region - Pengyu Li; Keyan Guo; Yaokun Fu; Gensheng Li (Journal of Cleaner Production, 2026)

Innovative for farmland reclamation: Optimizing earthwork allocation and elevation in mining-induced subsidence - Zhuo Wang; Gensheng Li; Junjiang Liu; Keyan Guo; Honglin Liu; Tenghao Wang; Jinmao Ju; Junhui Zhang (Journal of Environmental Management, 2025)

Coffin timber from southeastern China as a tree-ring archive for paleoclimate research - Zepeng Mei; Xin Jia; Duo Zheng; Feifei Zhou; Yu Xiao; Linping Ren; Wanru Tang; Di Zhang; Zhongcai Xiao; Min Zhou; Ting Guo; Xinyuan Kong; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Innovation for mine reclamation: Improving the reclamation efficiency and cropland rate in mining subsidence areas - Gensheng Li; Keyan Guo; Zhenqi Hu; Zhuo Wang; Wenjuan Wang; Yaokun Fu; Jinmao Ju; Junhui Zhang (Journal of Cleaner Production, 2025)

Associations of long-term exposure to fine particulate matter and its components with ovarian aging: Evidence from a cross-sectional study in China - Zifeng Cao; Xinyi Wu; Hongyuan Liu; Keyan Xu; Yehuan Yang; Manting Yang; Daimin Wei; Shidou Zhao; Xue Jiao; Qi Zhao; Ruimin Zheng; Yingying Qin; et al. (Journal of Hazardous Materials, 2025)

The negative effects of competition on tree resilience weakened as drought severity intensified - Xinyu Han; Lushuang Gao; Xianliang Zhang; Keyan Fang; Sijie Li; Keda Cui; Mengzhao Guo; Xiuhai Zhao (Agricultural and Forest Meteorology, 2025)

Deleterious variants in RNF111 impair female fertility and induce premature ovarian insufficiency in humans and mice - Chengcheng Song; Yingying Qin; Yan Li; Bingyi Yang; Ting Guo; Wenqing Ma; Dian Xu; Keyan Xu; Fangfang Fu; Li Jin; Yanhua Wu; Shuyan Tang; et al. (Science China Life Sciences, 2024)

ENSO weakens the co-variability between the spring persistent rains and Asian summer monsoon: Evidences from tree-ring data in southeastern China - Feifei Zhou; Keyan Fang; Fredrik Charpentier Ljungqvist; Tinghai Ou; Jun Cheng; Fen Zhang; Zhengtang Guo (Journal of Hydrology, 2024)

Modulations of NAO on the interplay between monsoon and westerlies in Asia on interdecadal timescales - Qichao Yao; Ben Zheng; Keyan Fang; Amy Hudson; Feifei Zhou; Haonan Chen; Haiming Tan; Futao Guo; Valerie Trouet (Climate Dynamics, 2024)

Indian summer monsoon drives synchronous interdecadal hydroclimate changes in the Tibetan Plateau and surroundings - Keyan Fang; Zepeng Mei; Hao Wu; Feifei Zhou; Heikki Seppä; Zhengtang Guo (Global and Planetary Change, 2024)

In-situ construction of BiOBr/Bi2WO6 S-scheme heterojunction nanoflowers for highly efficient CO2 photoreduction: Regulation of morphology and surface oxygen vacancy - Jiaming Wu; Keyan Li; Siyu Yang; Chunshan Song; Xinwen Guo (Chemical Engineering Journal, 2023)

Host-induced gene silencing of brown planthopper glutathione S-transferase gene enhances rice resistance to sap-sucking insect pests - Jun Yang; Xiao-Qin Sun; Keyan Zhu-Salzman; Qing-Ming Qin; Hui-Qiang Feng; Xiang-Dong Kong; Xu-Guo Zhou; Qing-Nian Cai (Journal of Pest Science, 2021)

Biodegradable chitosan-ethylene glycol hydrogel effectively adsorbs nitrate in water - Changhong Chen; Yiwei Guo; Li Long; Keyan Chen; Xiaolan Hu; Yingwen Xue (Environmental Science and Pollution Research, 2020)

Interdecadal modulation of the Atlantic Multi-decadal Oscillation (AMO) on southwest China’s temperature over the past 250 years - Keyan Fang; Zhengtang Guo; Deliang Chen; Lei Wang; Zhipeng Dong; Feifei Zhou; Yan Zhao; Jinbao Li; Yingjun Li; Xinguang Cao (Climate Dynamics, 2019)

An interdecadal climate dipole between Northeast Asia and Antarctica over the past five centuries - Keyan Fang; Deliang Chen; Zhengtang Guo; Yan Zhao; David Frank; Maosheng He; Feifei Zhou; Feng Shi; Heikki Seppä; Peng Zhang; Raphael Neukom (Climate Dynamics, 2019)

Intensified variability of the El Niño–Southern Oscillation enhances its modulations on tree growths in southeastern China over the past 218 years - Lei Wang; Keyan Fang; Dai Chen; Zhipeng Dong; Feifei Zhou; Yingjun Li; Peng Zhang; Tinghai Ou; Guoyang Guo; Xinguang Cao; Mingtong Yu (International Journal of Climatology, 2018)
Lack of long‐term tree‐ring records in the core regions of the Asian summer monsoon in southeastern China limits our ability of evaluating the current climate change in a historical context. In this study, we developed the first 218‐year tree‐ring chronology (1798–2015) of Pinus massoniana in Zhangping area, Fujian Province, humid subtropical China. This chronology is positively correlated with winter–spring (January–March) temperature ( r = 0.359, p r = 0.351, p r = 0.30, N = 66) matches closely with the ENSO variability during 1950–2015. The modulations of the ENSO on regional tree growth have been the most conspicuous since the 1950s, which corresponds to its enhanced inter‐annual variability. The extreme growth anomalies match quite well with the extreme years of the moisture‐sensitive chronologies. The dry epoch from 1935 to 1958 is the most severe long‐lasting drought in our tree rings, which is a widely distributed pattern in southeastern China and is likely modulated by the La Niña‐like modes in that period.

Drought variation of western Chinese Loess Plateau since 1568 and its linkages with droughts in western North America - Keyan Fang; Zhengtang Guo; Deliang Chen; Hans W. Linderholm; Jinbao Li; Feifei Zhou; Guoyang Guo; Zhipeng Dong; Yingjun Li (Climate Dynamics, 2017)

Interannual to centennial variability of the South Asian summer monsoon over the past millennium - Feng Shi; Keyan Fang; Chenxi Xu; Zhengtang Guo; H. P. Borgaonkar (Climate Dynamics, 2017)

Abrupt vegetation shifts caused by gradual climate changes in central Asia during the Holocene - Yan Zhao; YaoLiang Liu; ZhengTang Guo; KeYan Fang; Quan Li; XianYong Cao (Science China Earth Sciences, 2017)

Pea aphid promotes amino acid metabolism both in M edicago truncatula and bacteriocytes to favor aphid population growth under elevated CO 2 - Huijuan Guo; Yucheng Sun; Yuefei Li; Bin Tong; Marvin Harris; Keyan Zhu‐Salzman; Feng Ge (Global Change Biology, 2013)
Rising atmospheric CO 2 levels can dilute the nitrogen ( N ) resource in plant tissue, which is disadvantageous to many herbivorous insects. Aphids appear to be an exception that warrants further study. The effects of elevated CO 2 (750 ppm vs. 390 ppm) were evaluated on N assimilation and transamination by two M edicago truncatula genotypes, a N‐fixing‐deficient mutant ( dnf1 ) and its wild‐type control (Jemalong), with and without pea aphid ( Acyrthosiphon pisum ) infestation. Elevated CO 2 increased population abundance and feeding efficiency of aphids fed on Jemalong, but reduced those on dnf1 . Without aphid infestation, elevated CO 2 increased photosynthetic rate, chlorophyll content, nodule number, biomass, and pod number for Jemalong, but only increased pod number and chlorophyll content for dnf1 . Furthermore, aphid infested Jemalong plants had enhanced activities of N assimilation‐related enzymes (glutamine synthetase, Glutamate synthase) and transamination‐related enzymes (glutamate oxalate transaminase, glutamine phenylpyruvate transaminase), which presumably increased amino acid concentration in leaves and phloem sap under elevated CO 2 . In contrast, aphid infested dnf1 plants had decreased activities of N assimilation‐related enzymes and transmination‐related enzymes and amino acid concentrations under elevated CO 2 . Furthermore, elevated CO 2 up‐regulated expression of genes relevant to amino acid metabolism in bacteriocytes of aphids associated with Jemalong, but down‐regulated those associated with dnf1 . Our results suggest that pea aphids actively elicit host responses that promote amino acid metabolism in both the host plant and in its bacteriocytes to favor the population growth of the aphid under elevated CO 2 .